Rediscovering of Chara braunii (Characeae, Charophyta) in Madeira (Macaronesian region, Portugal) - Medina, Leopoldo; Nascimento, Pedro; Menezes de Sequeira, Miguel (Botanica Complutensis, 2021)
Chara braunii C.C. Gmelin (Characeae, Charophyta) was found in Madeira Island (Portugal) in a water channel in an agricultural area. This constitutes the first record of that species since 1944 in the Macaronesian region (Azores, Madeira and Canary archipelagos).